2019
DOI: 10.1186/s12886-019-1204-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of extended depth of focus intraocular lenses in cataract surgery: a systematic review and meta-analysis

Abstract: Background This study aims to evaluate the efficacy and safety of extended depth of focus (EDOF) intraocular lenes (IOLs) in cataract surgery. Methods All comparative clinical trials that involved bilaterally implanting EDOF IOLs in patients with cataract were retrieved from the literature database. We used random effects models to pool weighted mean differences (WMD) and risk ratio (RR) for continuous and dichotomous variables, respectively. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
4
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 27 publications
2
59
4
10
Order By: Relevance
“…Consequently, the conclusions of most studies were inconsistent or with inadequate methodology. In contrast with the previous meta-analysis 26 , our results showed a higher incidence of halos in trifocal IOLs. Trifocal IOLs, by design, were inevitably associated with 18% to 20% loss in light transmission, leading to a relatively blurred image 35 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Consequently, the conclusions of most studies were inconsistent or with inadequate methodology. In contrast with the previous meta-analysis 26 , our results showed a higher incidence of halos in trifocal IOLs. Trifocal IOLs, by design, were inevitably associated with 18% to 20% loss in light transmission, leading to a relatively blurred image 35 .…”
Section: Discussioncontrasting
confidence: 99%
“…Intermediate distance VA has been given heightened importance since most daily routine activities, such as driving, working and operating electronic devices, are performed at an intermediate distance. In the present meta-analysis, the hybrid multifocal-EDOF IOL yielded better UIVA than trifocal IOLs, which was not observed in the previous meta-analysis 26 . This finding was supported by the defocus curve in some studies, which showed that the hybrid multifocal-EDOF IOL performed better at the defocus level from -1.5D to -1D 4 , 11 , 13 , 19 , 20 .…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…[11][12][13] In addition, their impact on the quality of vision has been clinically studied through the visual acuity and contrast sensitivity, as well as the incidence rate of photic phenomena (e.g., halos, flashes, starbursts, and glare). [14][15][16] The three IOLs were taken from random batches. Figure 3a shows the normalized central intensities of the recorded disks as function of their radius for each IOL and the reference lens (as baseline) in their main focal planes.…”
Section: Tested Iolsmentioning
(Expert classified)
“… 1 , 2 Extended depth of focus (EDOF) IOLs is one of these options for presbyopia correction that has experienced a prolific development in recent years. 3 The basic principle behind these IOLs is to create a single elongated focal point to enhance the depth of focus or range of vision, allowing a functional vision at different distances in presbyopia. 4 This effect can be achieved by inducing controlled levels of spherical aberration, 5 combining refractive and diffractive surfaces to optimize achromatic and chromatic aberrations 6 , 7 or using a pinhole design.…”
Section: Introductionmentioning
confidence: 99%